The Great Chicago Fire : rising from the ashes - Hannigan, Kate (History comics (First Second (Firm)), 2020)
As fire engulfs the city of Chicago, Illinois, during the Great Chicago Fire, brother and sister, J.P. and Franny, and their dog must traverse the city to reunite with their parents.